Peran Sistem Pengendalian Internal dalam Pencegahan Fraud Pada Bank Syariah - Pratiwi, Annisa Adhelia; Septianingsih, Aulia Rahma; Amalia, Della; Utama, Fikri Rizki (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study discusses the role of internal control systems in fraud prevention in Islamic banks. The research uses a qualitative descriptive approach to understand the implementation of internal control systems in maintaining operational effectiveness and preventing fraudulent activities within Islamic banking institutions.Data collection was conducted through documentation studies and literature reviews from journals, books, and related scientific sources. The results of this study indicate that the internal control system has an important role in preventing fraud through transaction supervision, separation of duties, authorization systems, periodic evaluations, and the implementation of operational procedures in accordance with sharia principles. Internal control systems also help management identify risks and minimize opportunities for fraud. In addition, the use of information technology systems and routine supervision supports the effectiveness of fraud prevention efforts in Islamic banking institutions. However, the study also found several obstacles in implementing internal control systems, including limited human resources, low employee awareness regarding compliance, technological developments that increase fraud risks, and weak supervision in certain operational activities. Therefore, strengthening internal control systems and increasing employee competence are important steps to support effective fraud prevention in Islamic banks.